Reasons and Countermeasures for Some Middle School Students' Failure to Achieve Higher Physics Scores - Zheng, Qianru (Journal of Education and Educational Technologies, 2023)
This paper will introduce an intelligent automatic control air conditioning system, based on STC89C52RC single chip microcomputer. It can check the ambient temperature, the number of people and display temperature and number of people to set the temperature alarm value of the system up and down limit parameters for the realization of air conditioning automatic refrigeration and heating. The system is practical and has certain application value. This paper distinguishes price-based monetary policy from quantitative monetary policy, and studies the impact of monetary policy fluctuations on the dynamic adjustments of capital structure. The results show that tight monetary policy will reduce the speed of capital structure adjustment, loose monetary policy will accelerate the speed of capital structure adjustment under price-based monetary policy and quantitative monetary policy; Compared with state-owned enterprises, capital structural adjustment of non-state-owned enterprises is more sensitive to monetary policy fluctuations. This study provides empirical evidence for the analysis of the micro-effects of macro-monetary policy, and provides reference for enterprises to optimize their capital structure.